Empires, Nations, and Natives : Anthropology and State-Making - Sigaud, Lygia; Neiburg, Federico G.; L'Estoile, Benoit de (Book collections on Project MUSE., 2005)
By drawing on the social history of the social sciences, the sociology of scientific knowledge, and the ethnography of the State, these essays show how anthropology and state-building should be considered as intertwined processes.